On the tasks of humanistic Psychology - Blaustein, Leopold (Phainomena (Ljubljana), 2025)
The essay examines the theoretical basics and methodological framework of humanistic psychology, a psychological approach that investigates experiential wholes of higher order within humanistic reality. In contrast to non-humanistic psychology, which focuses on elementary lived experiences in isolation, humanistic psychology emphasizes the study of complex psychological phenomena as they emerge in relation to cultural artefacts, social relationships, and creative processes. The paper argues that humanistic psychology serves as an auxiliary science for the humanities, while maintaining methodological pluralism in its investigative approaches.
Keywords: cultural artefacts; experiential wholes of higher order; humanistic psychology; humanistic reality; humanistična psihologija; humanistična resničnost; izkustvene celote višjega reda; kulturni artefakti; razumevanje; understanding